Global Exponential Stability of Almost Periodic Solutions for Nicholson’s Blowflies System with Nonlinear Density-Dependent Mortality Terms and Patch Structure - Liu, Pengyan; Zhang, Liang; Liu, Shitao; Zheng, Lifei (Mathematical Modelling and Analysis, 2017)
This paper considers a generalized Nicholson’s blowflies system with nonlinear density-dependent mortality terms and patch structure. Under appropriate conditions, we establish some criteria to ensure that the solutions of this system exist and converge globally exponentially to a positive almost periodic solution. The results complement another case of nonlinear density-dependent mortality terms in Chen and Wang [5].